Status of the Level of Transversal Competencies of Secondary Science Students - Saima Hamid, (JSE, 2024)
This research was designed to assess the current status of the level of Transversal Competencies (TVCs) of secondary science students. This study focused on a single variable of Transversal competencies discussed under six domains, first one was critical and innovative thinking, second one was interpersonal skills, third one was intrapersonal skills, fourth one was global citizenship, next one was information literacy (IL) and media, and the last and the sixth domain, was related to religious values and physical health (United Nations Educational, Scientific, and Cultural Organization Bangkok, 2015, 2016). Transversal competencies were defined under the above-mentioned domains, in the framework presented by UNESCO in collaboration with ERI-Net (Education Research Institute Network). It was a descriptive self-reported survey study. All secondary science students studying in schools in the Islamabad territory were the population of this research. The technique used to select the sample of this study was multistage random sampling. One questionnaire was developed for this study, having 74 statements to assess these competencies. A panel of experts ensured the validity of scales, Content Validity Index was calculated, which showed the tool was excellent. For reliability, Cronbach's alpha was calculated to measure internal consistency. Internal consistency of each domain was calculated separately, and the results were satisfactory. The researcher visited the schools to collect the data. Data was analyzed by using descriptive statistics. Mean and standard deviation (SD) statistical analysis were used for the results. The results elaborated that secondary science students are at an intermediate level in their Transversal competencies.